PERAN KAMPUS SEBAGAI UPAYA NON PENAL DALAM PEMBERANTASAN PENYALAHGUNAAN NARKOTIKA - Muhamad Romdoni (Gapenas Publisher, 2022)
This research was conducted to find out how the campus actions as a non-penal effort in eradicating narcotics abuse. By using the normative juridical method, namely reviewing the norms in positive law, the approach in this research is statutory and uses secondary material as a source in research. It can be concluded that the campus as an educational environment if you want to produce outstanding graduates, must take good care of the behavior of its students, both academic and non-academic. In the non-academic field, campuses can ensure that their students are free from narcotics abuse by making preventive efforts (non-penal efforts) as a follow-up to the Presidential Instruction of the Republic of Indonesia Number 6 of 2018 campuses can carry out several non-penal efforts including legal advocacy, formation of cadres, information dissemination and reporting